Compression Stress-Induced Internal Magnetic Field in Bulky TiO2 Photoanodes for Enhancing Charge-Carrier Dynamics - Wu, B.; Lyu, Y.; Chen, W.; Zheng, J.; Zhou, H.; De Marco, Roland; Tsud, N.; Prince, K.C.; Kalinovych, V.; Johannessen, B.; Jiang, San Ping; Wang, S. (2023)
Enhancing charge-carrier dynamics is imperative to achieve efficient photoelectrodes for practical photoelectrochemical devices. However, a convincing explanation and answer for the important question which has thus far been absent relates to the precise mechanism of charge-carrier generation by solar light in photoelectrodes. Herein, to exclude the interference of complex multi-components and nanostructuring, we fabricate bulky TiO2 photoanodes through physical vapor deposition. Integrating photoelectrochemical measurements and in situ characterizations, the photoinduced holes and electrons are transiently stored and promptly transported around the oxygen-bridge bonds and 5-coordinated Ti atoms to form polarons on the boundaries of TiO2 grains, respectively. Most importantly, we also find that compressive stress-induced internal magnetic field can drastically enhance the charge-carrier dynamics for the TiO2 photoanode, including directional separation and transport of charge carriers and an increase of surface polarons. As a result, bulky TiO2 photoanode with high compressive stress displays a high charge-separation efficiency and an excellent charge-injection efficiency, leading to 2 orders of magnitude higher photocurrent than that produced by a classic TiO2 photoanode. This work not only provides a fundamental understanding of the charge-carrier dynamics of the photoelectrodes but also provides a new paradigm for designing efficient photoelectrodes and controlling the dynamics of charge carriers.